KELUARGA DAN IMPLIKASINYA TERHADAP PENDIDIKAN: PENDEKATAN TAFSIR MAUDHU’I - Fajar Indarsih (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Association of Muslim Community in ASEAN (AMCA), 2018)
Family is the first place for education for the development and growth of children. Salafi scholars recommend that parents, especially when the child is 7 years old and above, be educated and teach worship practices and kindnesses, such as being invited to congregation to the nearest mosque, or prayer room. The aim is for children to get used to worship practices from childhood, as a basis for their growth in the following years. Not only there, even when a child is 10 years old (early age ballig) and does not want to carry out the obligation to worship, parents have the right to give the right to punish their children, such as hitting that does not exceed the limits and does not interfere with their psychic. This means that the implications of the family for education are enormous.